Circadian gene variants and the skeletal muscle circadian clock contribute to the evolutionary divergence in longevity across Drosophila populations - Hunt, Liam C.; Jiao, Jianqin; Wang, Yong-Dong; Finkelstein, David; Rao, Deepti; Curley, Michelle; Robles-Murguia, Maricela; Shirinifard, Abbas; Pagala, Vishwajeeth R.; Peng, Junmin; Fan, Yiping; Demontis, Fabio (Genome Research, 2019)
Organisms use endogenous clocks to adapt to the rhythmicity of the environment and to synchronize social activities. Although the circadian cycle is implicated in aging, it is unknown whether natural variation in its function contributes to differences in lifespan between populations and whether the circadian clock of specific tissues is key for longevity. We have sequenced the genomes of Drosophila melanogaster strains with exceptional longevity that were obtained via multiple rounds of selection from a parental strain. Comparison of genomic, transcriptomic, and proteomic data revealed that changes in gene expression due to intergenic polymorphisms are associated with longevity and preservation of skeletal muscle function with aging in these strains. Analysis of transcription factors differentially modulated in long-lived versus parental strains indicates a possible role of circadian clock core components. Specifically, there is higher period and timeless and lower cycle expression in the muscle of strains with delayed aging compared to the parental strain. These changes in the levels of circadian clock transcription factors lead to changes in the muscle circadian transcriptome, which includes genes involved in metabolism, proteolysis, and xenobiotic detoxification. Moreover, a skeletal muscle-specific increase in timeless expression extends lifespan and recapitulates some of the transcriptional and circadian changes that differentiate the long-lived from the parental strains. Altogether, these findings indicate that the muscle circadian clock is important for longevity and that circadian gene variants contribute to the evolutionary divergence in longevity across populations.